Performance and Combustion Process of a Dual Fuel Diesel Engine Operating with CNG-Palm Oil Biodiesel - Ahmad Arbi Trihatmojo; Bambang Sudarmanta; Oki Muraza (Politeknik Perkeretaapian Indonesia Madiun, 2023)
Efforts to build and develop a low-emission transportation system have been carried out, one of which is by applying biodiesel and gas to dual-fuel diesel engines. Biodiesel is an oxygenated, low-sulfur, and high flash point alternative diesel fuel. In the dual fuel mode, CNG is used as a substitute fuel and palm biodiesel as a combustion pilot which is injected directly into the combustion chamber at 13 °CA BTDC. CNG injection timing was 110 °CA ATDC and the CNG injection duration was gradually increased. Performance and combustion processes in single-fuel mode and dual-fuel mode are compared. The engine was kept at a constant speed of 2000 rpm at all load conditions. The results show that the dual fuel mode at low and medium loads produces in-cylinder pressure and the heat release rate is lower than the single fuel mode, but at high loads, it produces in-cylinder pressure and the heat release rate is 5.14% greater. CO and HC emissions produced by the dual fuel mode are higher than the single fuel mode at all loads. conversely, the dual-fuel mode produces 95.58% lower smoke emissions than the single-fuel mode at all loads.